The cooler - Furst, Sean.; Pierce, Michael; Hannah, Frank, 1971-; Kramer, Wayne, 1965-; Macy, William H., 1950-; Bello, Maria, 1967-; Hatosy, Shawn, 1975-; Livingston, Ron.; Warren, Estella; Nascarella, Arthur J.; Gainey, M. C.; Sorvino, Paul.; et al. (Santa Monica, CA : Lions Gate Home Entertainment, 2004)
Bernie is extremely unlucky at gambling and he owes the Shangri-La casino's mob boss Shelly Kaplow over $100,000. He is so unlucky that he is hired as a "cooler". He gambles next to high rollers and gives them some of his bad luck to stop them from winning. This arrangement works out for awhile, but when Bernie has almost paid off his debt, he meets cocktail waitress, Natalie. The two start to fall in love and Bernie's luck begins to change. Unfortunately, Shelly isn't going to let Bernie go so easily.
Originally released as a motion picture in 2003.
English track: Dolby digital 5.1.
Commentary: Dolby digital 2.0.
Music track: Dolby digital 5.1.
Special features: Director and crew commentaries; Anatomy of a scene; Storyboard comparisons; 5.1 music only track.
Director of photography, James Whitaker ; editor, Arthur Coburn ; music, Mark Isham ; costume designer, Kristin M. Burke ; production designer, Toby Corbett.
Keywords: Casinos -- Employees -- Drama; Organized crime -- Nevada -- Las Vegas -- Drama; Man-woman relationships -- Nevada -- Las Vegas -- Drama; Feature films; Comedy films; Films for the hearing impaired